2015
DOI: 10.1080/10408398.2012.755947
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Mean Intensity of Anisakidae Parasite in Seafood Caught in the Mediterranean Sea Focusing on Fish Species at Risk of Being Raw-consumed. A Meta Analysis and Systematic Review

Abstract: SummaryObjective: to assess the prevalence and the mean intensity of anisakids in seafood caught in Mediterranean sea, focusing on fish species at risk of being raw-consumed. Results: twelve studies were identified. Among them four studies considered fish species which are often consumed raw or lightly preserved or not thoroughly cooked anchovy, pilchard and Atlantic mackerel. Data synthesis: all pooled analyses were based on random-effect model.Anisakids prevalence in fish muscle was 0.64% (P < 0.0001), in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…The infection appears to be more frequent in coastal areas, where there is a higher tendency to consume seafood. The results of the present retrospective study are in agreement with other studies claiming that the disease is more widespread in the regions of Southern and Central Italy (Abruzzo, Molise, Campania, Puglia, and Sicily) [ 34 ]. On the contrary, no marked geographical differences were found in the recent study conducted in France [ 119 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The infection appears to be more frequent in coastal areas, where there is a higher tendency to consume seafood. The results of the present retrospective study are in agreement with other studies claiming that the disease is more widespread in the regions of Southern and Central Italy (Abruzzo, Molise, Campania, Puglia, and Sicily) [ 34 ]. On the contrary, no marked geographical differences were found in the recent study conducted in France [ 119 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the strict selection applied, the number of cases detected is higher than the number indicated in other recent Italian studies [ 34 , 38 ]. In addition, although great efforts were made during the bibliographic investigation, it is known that other cases (not described in the literature) are also reported annually by the health authorities, mainly in regions of Central and Southern Italy [ 38 ].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, there is a wide range of research available concerning the nematodes that infect anchovy and sardine in the Mediterranean (e.g. Rello et al 2009;Gutiérrez-Galindo et al 2010;Cavallero et al 2015;Zorica et al 2016) and, in general, such studies have reported a relatively low prevalence of nematodes in these two species, ranging from 0 to 25%, with low values for overall prevalence when data from different studies were pooled (<3% in the case of Anisakids in the meta analysis conducted by Colombo et al 2016). In a study by Rello et al (2008), H. aduncum was the only Anisakid parasite found in sardines from the southern and eastern coasts of Spain, with a total prevalence of 11.85%.…”
Section: Parasitismmentioning
confidence: 99%
“…Cipriani et al, 2016; Daschner et al, 1998; Mattiucci et al, 2013). In fact, even though according to a recent systematic review(Colombo et al, 2016) the overall prevalence values are quite low, particularly high values have been reported in some areas, such as in Sardinia (Piras et al, 2014) and Croatia (Mladineo and Poljak, 2014). The zoonotic infection, known as anisakidosis, is acquired through the consumption of raw or undercooked marine fish or cephalopods infected by third stage larvae of Anisakidae nematodes, most frequently belonging to Anisakis and Pseudoterranova genera (Lymbery and Cheah, 2007).…”
mentioning
confidence: 98%